Penekanan Anggaran, Kapasitas Individu dan Asimetri Informasi memoderasi Partisipasi Penganggaran terhadap Senjangan Anggaran - Purba Dwiyanthi, Ida Ayu Made; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p06, 2022)
The budget that is not absorbed effectively causes a budget gap in the Perumda Water Drinking Tirta Sewakadarma. The aim of the study is to obtain empirical evidence regarding the effect of budget emphasis, individual capacity and information asymmetry on moderating budgetary participation on budgetary gaps. The research sample was 50 respondents with purposive sampling method of determining the sample. Data was collected by distributing questionnaires. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that budget participation had a significant positive effect on the budget gap. Budget emphasis and individual capacity are able to moderate budgetary participation towards budgetary gaps. Information asymmetry is not able to moderate the effect of budget participation on the budget gap. Keywords: Budget Participation; Budget Emphasi;, Individual Capacit;, Information Asymmetry; Budgetary Slack.